Artisanal Crude Refining in Niger Delta and its Impact on the Cultural and Religious Beliefs of the People - John, Elizabeth Okon; Nnadozie, Juongwa (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2021)
In the discourse on the impact of artisanal crude refining on the natural environment in the Niger Delta, the resultant effects of the environmental degradation on the traditional religious and cultural beliefs of the natives have been ignored. Against this backdrop, this paper aims at bringing to the fore the impact of artisanal crude refining activities on the traditional religious and cultural beliefs of the natives of the host communities. The paper adopts the analytical method in its investigation of the subject matter. It also adopts the tools of logical and critical evaluation. The investigation is limited to communities in Delta, Rivers and Bayelsa states of Nigeria. The paper submits that though most indigenes attribute the cause of the decline in traditional religious and cultural beliefs to the advent of Christianity in the region, the environmental degradation associated with oil exploration activities also plays a significant role in the decline of these beliefs.